Implementation of the Learning Management Model Based on Cognitive Development Theory to Enhance Mathematical Problem-Solving Ability for Prathomsuksa 6 Students - Kanjana Ninnuan,; Montree Wongsaphan, (Journal of Educational Issues, 2024)
This study investigates the implementation of the learning management model based on cognitive development theory to enhance mathematical problem-solving ability for Prathomsuksa 6 students. The sample group assigned by cluster random sampling was thirty Prathomsuksa 6 students of Chumchon Yot Kaeng Songkhro School. The research instruments consist of learning achievement tests and mathematical problem-solving ability tests (pre-test and post-test). The statistical analyses were percentage, mean, standard deviation, and t-test (dependent samples) was employed for testing hypothesis. The results showed that students’ learning achievement after learning with the learning management model was significantly higher than before learning at a statistical level of .05. Also, the students had the mathematical problem-solving ability after learning significantly higher than before learning at a .05 level. When considering in each aspect, it was found that all of the mathematical problem-solving ability after learning was higher than before learning at a statistical level of .05, namely, 1) finding of the problem relationship; 2) writing of mathematical diagrams; 3) problem solving; and 4) traceability.